Unknown mucous structures of the members of genus Stichococcus Nägeli (Chlorophyta) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The results of study of 26 strains of green algae from ACKU collection represented by original isolates as well as by subcultures deposited in international collections of strains of the genus Stichococcus Nägeli (including 10 strains deposited as non-authentic culture of nomenclature type of this genus – S.bacillaris Nägeli), are reported. In 18 strains (including 7 strains of S.bacillaris) previously undescribed mucous structures have been founded. There are colonial mucilage, mucous sheath, mucous grains and mucous caps whose presence is inconsistent with the author’s diagnosis of this genus. The presence of mucous structures in most of the represented in international collections strains of the genus Stichococcus confirms the assumption of phylogenetic heterogeneity of this genus at the phenotypic level.
Keywords: Chlorophyta, Stichococcus, Stichococcus bacillaris, mucous structure, morphology, systematics, culture of microalgae.